Why Are International Visitors More Satisfied with the Tourism Experience? The Role of Hedonic Value, Escapism, and Psychic Distance. (November 2021) - Ponsignon, Frédéric; Lunardo, Renaud; Michrafy, Mohamed
Previous studies have consistently observed that international visitors are more satisfied with the tourism experience than their domestic counterparts. To date, however, no study has provided empirical evidence of the mechanism that could explain this phenomenon. Building on the experiential paradigm, we conducted two empirical studies (a field study and an online experiment) showing that the reason foreign (vs. domestic) visitors exhibit higher levels of satisfaction lies in the greater hedonic value that these tourists derive from their experience. Moreover, the greater hedonic value observed among international foreign visitors is due to the deeper feeling of escapism they experience by traveling abroad. We also demonstrate that this effect is explained by the concept of psychic distance, whereby going abroad leads to a greater perception of psychic distance, and subsequently escapism, hedonic value, and satisfaction with the tourism experience.